2020
DOI: 10.3390/jcm9010227
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine to Body Weight Ratio Is Associated with Incident Diabetes: Population-Based Cohort Study

Abstract: We investigated the association between creatinine to body weight (Cre/BW) ratio and incident diabetes. In this cohort study, 9659 men and 7417 women were follow up mean (SD) 5.6 (3.5) years and 5.4 (3.4) years, respectively. For men, tertile 1 (T1; n = 3176), Cre/BW < 0.01275; tertile 2 (T2; n = 3258), 0.01275 ≤ Cre/BW < 0.0148; and tertile 3 (T3; n = 3225), Cre/BW ≥ 0.0148; and for women, T1 (n = 2437), Cre/BMI < 0.0118; T2 (n = 2516), 0.0118 ≤ Cre/BMI < 0.014; and T3 (n = 2477), Cre/BMI ≥ 0.014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The mechanism about the relationship of the Cr/BW ratio with the incident NAFLD remains largely unknown. We suggest that this relationship could be mediated by insulin resistance because a lower Cr/BW ratio has been shown to increase the risk of DM in a recent study [23]. Concretely, SMI is a potent indicator of insulin resistance [30], and insulin resistance makes a great contribution to the incident NAFLD among nonobese individuals without DM [31].…”
Section: Gastroenterology Research and Practicementioning
confidence: 78%
See 1 more Smart Citation
“…The mechanism about the relationship of the Cr/BW ratio with the incident NAFLD remains largely unknown. We suggest that this relationship could be mediated by insulin resistance because a lower Cr/BW ratio has been shown to increase the risk of DM in a recent study [23]. Concretely, SMI is a potent indicator of insulin resistance [30], and insulin resistance makes a great contribution to the incident NAFLD among nonobese individuals without DM [31].…”
Section: Gastroenterology Research and Practicementioning
confidence: 78%
“…Among individuals with normal renal function, the use of serum creatinine (Cr) has been proposed as an inexpensive and easily obtainable surrogate index to evaluate the skeletal muscle mass [21,22]. Recently, an interesting novel index named the Cr to body weight (Cr/BW) ratio has been demonstrated to be quite useful for the prediction of T2DM and NAFLD [23,24]. In fact, the positive relationship between Cr and body weight is even closer among nonobese individuals [20].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, studies investigating the association of Cre/BW and diabetes risks are sparse. Recently, a study conducted by Hashimoto et al [14] suggested that an independent association of diabetes risks with Cre/BW ratios in The NAGALA Study in Japan. Our ndings are similar to the result of Hashimoto and his colleagues.We observed that Cre/BW is negatively correlated with incident diabetes after handling missing value(HR: 0.268; 95% CI:0.229 to 0.314), and it also makes sense in different genders(HR = 0.255;95%CI: 0.212-0.307 in men and HR = 0.297;95%CI: 0.218-0.406 in women).Moreover, we found a nonlinear between Cre/BW and incident of diabetes using a cubic spline smoothing technique(after adjusting age,gender,SBP,DBP,FPG,TC,LDL,smoking and drinking status,family history of diabetes), and the effect sizes on the left and right sides of the in ection point was not consistent [left(HR: 0.13, 95%CI: 0.10-0.16,P < 0.0001);right(HR: 0.62, 95%CI: 0.46-0.82,P = 0.0008)].…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al proved Cre/BW ratios may predict future diabetes risks and is inversely related to incident diabetes in the Japanese population who underwent a medical health check-up program [14]. However, there is no report about Cre/BW ratios with diabetes to date in Chinese people, to address these issues, we conducted a study to investigate the relationship between Cre/BW ratios and incident of diabetes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation